Productivity and environmental implications of fodder beet and maize silage as supplements to pasture for late lactation dairy cows. Issue 1 (2nd January 2020) - Dalley, Dawn; Waugh, Deanne; Griffin, Amelia; Higham, Caleb; de Ruiter, John; Malcolm, Brendon
ABSTRACT: A short-term, dairy cow, grazing experiment was conducted in late-lactation (autumn) to determine the effect of fodder beet (FB) and maize silage supplementation on dry matter and nitrogen (N) intake, urinary N excretion and milk solids (MS; milk fat + milk protein) production. Seventy-two multiparous, lactating (224 ± 20.0 DIM; mean ± SD) Holstein-Friesian cows were randomly assigned ( n = 24 per treatment; 8 per replicate) to one of three groups. Control animals were offered pasture (11 kg DM/cow/day) with maize silage (4 kg DM/cow/day; 'Maize'). The other two groups were either offered pasture (11 kg DM/cow/day) with 25% FB (4 kg DM/cow/day; 'FB25') or pasture (9 kg DM/cow/day) with 40% FB (6 kg DM/cow/day; 'FB40'). At the same supplement DM intake, diets containing maize silage or grazed FB had similar urinary nitrogen (UN) concentrations, but FB increased milk solids (MS) production. At 40% FB inclusion UN excretion was reduced but this came at the expense of MS production. Farmers need to exhibit caution when feeding fodder beet to lactating dairy cows to minimise the risk of adverse animal health effects. Feeding fodder beet allocations high enough to achieve significant environmental benefit is likely to compromise animal health and milk production.